ANALISIS PENDAPATAN OPERASIONAL KELOMPOK BANK BERDASARKAN MODAL INTI IV DI INDONESIA - Dewanti Anis Nafissyah (2022)
Bank is a financial institution whose activities are to collect funds, distribute funds and provide other financial services. All activities carried out by the bank are the bank's business to make a profit. Bank profits are obtained when the income earned is greater than the costs incurred. There are several sources of bank operating income, namely spread based income and fee based income. Spread based income is income derived from interest such as credit interest income and interest income on securities, then fee based income is income obtained from the provision of other financial services and other operating income. Currently, banks do not only rely on income from loan interest, but also from other sources of income. As time goes by, technological developments are increasing, this causes banks to take advantage of technological developments to increase fee based income as a source of income.